Reconstructing Digital Ethics in Islamic Education through Az-Zarnuji’s Ta‘lim Al-Muta‘allim - Ngatmin Abbas; Amir Mahmud; M. Fatchurrohman (Universitas Islam Negeri Sumatera Utara, 2026)
Digital cultural transformation has changed the way students learn, communicate, and develop character. While this transformation offers new learning opportunities, it also creates ethical challenges, including misinformation, hate speech, cyber-violence, digital plagiarism, and the weakening of adab in academic interaction. This study focuses on reconstructing the principles of learning ethics in Az-Zarnuji’s Ta‘lim al-Muta‘allim into a digital ethics framework for Islamic education. Specifically, it examines five key principles: sincerity of intention, careful selection of teachers and learning environments, wara’ or moral caution, disciplined time management, and respect for the dignity of knowledge. This research employs a qualitative library-based method. The primary source is Ta‘līm al-Muta‘allim, while secondary sources include scholarly works on Islamic education, digital ethics, digital literacy, and digital citizenship. The data are analyzed through critical reading, thematic categorization, conceptual synthesis, and the mapping of classical ethical values into contemporary digital-ethics competencies. The findings indicate that Az-Zarnuji’s ethical principles can be reconstructed into a framework of “digital adab,” consisting of academic integrity, information prudence, communication ethics, disciplined digital time use, and responsibility for preserving the dignity of knowledge. This framework can be applied in Islamic Religious Education, school culture, family guidance, and the governance of educational technology use. Thus, Islamic education is positioned not merely to adapt to technological change but also to provide moral direction for shaping an ethical digital civilization.